III Semana Oceânica PB: Planet Ocean: the tides are changing (Environmental Smoke, 2023)
The theme of the III Semana Oceânica PB (III SOPB) was “Planet Ocean: the tides are changing”, taking into account the theme established by the United Nations (UN) in reference to Ocean Day. The event took place in person, in the municipalities of João Pessoa, Cabedelo, Lucena and Conde, with intermittent activities from June 7 to 18, 2023.The III SOPB is an initiative of the institutions (InPact and Associação Guajiru), in partnership with various entities from the public and private sectors and organized civil society. Its purpose is to create a space for collaborative dialogue between municipalities, the private sector, organized civil society and academia around the conservation and sustainable use of marine resources, as well as to promote Ocean Literacy on the Paraiba sea.In addition to the Sistema de Monitoramento da Fauna Marinha Paraibana (SISFAUMAR) - https://sisfaumar.com - we sought to promote new actions for the conservation of the coastal and marine environment, presenting to Paraiba society the Limpa Mar project by the Associação Guajiru and the Programa Estratégico de Estruturas Artificiais Marinhas da Paraíba (PREAMAR-PB).We said goodbye to this third year with talks, themed exhibitions, paddling with reef hugging, beach cleaning, a visit to a Brazilian Navy vessel, in short... an event full of ocean culture!